Elementary teachers‟ obstacles to design scientific paper during covid-19 - Dhiniaty Gularso; Ari Wibowo; Setyo Eko Atmojo (PROCEEDING UMSURABAYA, 2020)
Abstract. The process of disaster management of Covid-19 impacts the teacher motivation todesign scientific paper since the ministerial circular number 4 of 2020 dated March 24th 2020 which stated that learning is from home. Generally speaking, the obstacles of the elementary teachers in Indonesia are also found by the elementary teachers in cluster II, Kasihan Bantul, Yogyakarta, Indonesia for the process of paper designing, such as (1) less understanding on designing the scientific paper, (2) low motivation, (3) less information on the scientific journal that can be accessed, and (4) the allotted time. The problems that are faced by the teacher of Elementary School cluster II Kasihan bantul Yogyakarta Indonesia to design the paper during covid 19 are (1) teachers are fully concentrating on the online learning through Whatsapp, Google Classroom, Google Form and make the learning content on Youtube, (2) teachers are concentrating on the students‘ assessment. These obstacles, in general, can be solved by using topic of learning during Covid 19. For that purpose, it is required guidance for the elementary teachers to design scientific paper and choose the proper scientific journal. The roles of the Institute of Teacher‘s Education are expected by the elementary teachers.Keywords: Teachers‘ Obstacles, Elementary School, Scientific Paper Design, Pandemic of Covid 19